Faktor yang Mempengaruhi Perilaku Masyarakat Muslim Belum beralih dari Bank Konvensional ke Bank Syariah: Studi pada Masyarakat Kelurahan Panorama Kota Bengkulu - Dwi Afriani, Alya; Elwardh, Khairiah; Nurhab, Irpan (Economic Reviews Journal, 2025)
This study aims to determine the factors influencing the Muslim community in Panorama Village, Bengkulu City, not to switch from conventional banks to Sharia banks, and the most dominant factors. The method used was a qualitative approach with a phenomenological approach through interviews, observation, and documentation with 15 informants. The results showed seven factors influencing community decisions: knowledge, social factors, services and products, technology, promotion, reputation, and accessibility. Of these seven factors, the three most dominant were low knowledge, social influence, and minimal promotion of Sharia banks. This study concludes that limited literacy, social habits, and a lack of promotion are the main reasons why people continue to choose conventional banks.